The Clinical Application and Progress of Mirogabalin on Neuropathic Pain as a Novel Selective Gabapentinoids - Hui Tang; Jing Lu; Yazhuo Duan; Dejun Li (Hindawi Limited, 2023)
Background. Neuropathic pain is a complex sort of pain that is detrimental to individuals' health, both physically and mentally, but merely a small portion of them could witness pain alleviation. Mirogabalin, by distinctive binding characteristics of voltage-gated calcium channels, has won approval from the Japanese authority as a third member of gabapentinoids in Japan. Our review was aimed at encompassing the bulk of clinical research on mirogabalin, which included clinical trials, special considerations, coadministration studies, case reports, and cost-effectiveness studies. Methods. A review was carried out on a series of platforms, such as PubMed, MEDLINE, and Scopus, up to December 2021 using the keywords as follows: "mirogabalin OR mirogabalin besylate OR Tarlige OR DS-5565" AND "neuropathic pain OR Neuropathy." Results. Mirogabalin demonstrated analgesic activity and manageable adverse reactions and provides a new alternative for individuals with PHN or DPNP in 3 phase II and 4 III trials. Mirogabalin alleviated pain markedly in comparison with placebo. Administration of mirogabalin on a long-term basis is a flexible dosage regimen for patients with PHN. It is noteworthy that mirogabalin should be administrated cautiously when combined with probenecid and cimetidine on account of a slight increase in pharmacodynamics effects of mirogabalin. Conclusion. The development of mirogabalin allows further optimization of individual treatment strategies so as to provide more therapeutic choices in this medical domain.